PENDIDIKAN PLURALISME DALAM MEMBANGUN JATI DIRI BANGSA (Perspektif Agama Hindu) - I Gede Dedy Diana Putra; Kadek Agus Wardana; I Made Gede Nesa Saputra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
A country that has multiethnic and multimental uniqueness like Indonesia is faced with its own dilemma, on the one hand bringing Indonesia to become a great nation as a multicultural nation-state, but on the other hand it is a threat. So it is not an exaggeration to say that multicultural conditions are like coals in husks which are easily ignited and heat up at any time. Indonesia has great potential for conflicts between groups, ethnic groups, religions and ethnic groups. One of the indications is that various social, professional, religious, and organizations or groups have started to thrive and are struggling and acting on behalf of group interests which lead to SARA (ethnic, religious, racial and inter-group) conflicts. To produce valid and reliable data, this paper uses a qualitative writing style. In producing logical data, this paper performs several stages of data sorting in the form of: 1). Data reduction, 2). Display data, 3). Verifying data, and 4). Interpreting research data. In its presentation, measurable analysis becomes the basis for processing the data obtained. The perfection of this paper cannot be separated from the library technique which is carried out through an assessment of the existing literature on Google Scholar. Education is the spearhead that is able to restrain and eradicate all harmful doctrines of non-plural and non-multicultural actions which are very appropriate to be applied in the current era in preventing interests and combinations of intolerant understandings in the name of a religion. Strategies in school and implementing a curriculum that emphasizes pluralism and multiculturalism in the current era are very important to be followed up immediately so that misleading intellectual understanding does not multiply ingrained in students' understanding. The role of parents and teachers must be able and synergized in implementing an understanding of the concept of plurality and the plurality of a life so that later students or students understand differences and are able to re-instill heterogeneity. Hinduism in the scope of analysis of pluralism education highly appreciates social diversity. The concept of Hinduism which incidentally is very plural and in its holy book contains teachings about realizing tolerance, namely Widya, Maitri, Ahimsa, and Santi.